Pencirian hidrokimia air tanah dan air bawah tanah di Kerpan Kedah : Hydrochemichal characterization of soil water and groundwater of Kerpan - Umar Hamzah,; Yong, Cheng Yeu; Bashillah Baharudin,; Abdul Rahim Samsudin, (Universiti Kebangsaan Malaysia, 2008)
Chemical analysis was carried out on solution extracted from 85 soil samples collected at a prawn aquaculture in Kerpan. These soil samples were taken at depths of about 2 m by using hand auger. Localities of samples were along several parallel lines which are perpendicular to the coast to about 20 km towards inland. Water samples were also collected from boreholes drilled at depths of 10 to 25 m for chemical analysis. Hydrochemical data of water extracted from soil samples taken from depths of 1-2 m show chloride concentrations ranging from 12 to 6,500 mg/L. The wide range of ion concentrations indicates the presence of different type of water which can be classified as fresh to saline. Total dissolved solid values of the water samples also show quite a considerable range of concentrations ranging from 100 to 40,000 mg/L representing fresh to saline type of water. This saline zone is within about 1 km from the coast if interpreted based on total dissolved solid values while the distance is much further towards inland which is 4-5 km based on chloride concentrations. In coastal areas, the presence of salt water can be associated with direct intrusion of sea water into the underground water system or it can be contributed from the infiltration of sea water through the rivers or canals during high tides into the coastal plain. The presence of salt water is supported by the increase in the concentration of natrium, kalium and calcium towards the sea. Based on spatial distribution map of chloride concentration, high salinity contour seems to follow the shape of the aquaculture ponds in the study area indicating some possibility of infiltration of sea water in the pond into the neighbouring areas. Water samples from boreholes drilled to depths of 10 to 25 m were taken and analysed in order to detect for any influence of sea water intrusion into the salinity of groundwater in the study area. Borehole water samples show chloride concentration ranging from 2,030 to 13,000 mg/L while the concentration of total dissolved solid ranges from 3,233 to 9,280 mg/L. The high chloride and total dissolved solid concentrations in the samples indicate the areas near the boreholes or within 1 km from the coast were contaminated due to the intrusion of sea water.